Biomaterials-Based Regenerative Strategies for Skin Tissue Wound Healing - Kaur, Gurvinder; Narayanan, Ganesh; Garg, Deepa; Sachdev, Abhay; Matai, Ishita (ACS applied bio materials, 2022)
Skin tissue wound healing proceeds through four major stages, including hematoma formation, inflammation, and neo-tissue formation, and culminates with tissue remodeling. These four steps significantly overlap with each other and are aided by various factors such as cells, cytokines (both anti- and pro-inflammatory), and growth factors that aid in the neo-tissue formation. In all these stages, advanced biomaterials provide several functional advantages, such as removing wound exudates, providing cover, transporting oxygen to the wound site, and preventing infection from microbes. In addition, advanced biomaterials serve as vehicles to carry proteins/drug molecules/growth factors and/or antimicrobial agents to the target wound site. In this review, we report recent advancements in biomaterials-based regenerative strategies that augment the skin tissue wound healing process. In conjunction with other medical sciences, designing nanoengineered biomaterials is gaining significant attention for providing numerous functionalities to trigger wound repair. In this regard, we highlight the advent of nanomaterial-based constructs for wound healing, especially those that are being evaluated in clinical settings. Herein, we also emphasize the competence and versatility of the three-dimensional (3D) bioprinting technique for advanced wound management. Finally, we discuss the challenges and clinical perspective of various biomaterial-based wound dressings, along with prospective future directions. With regenerative strategies that utilize a cocktail of cell sources, antimicrobial agents, drugs, and/or growth factors, it is expected that significant patient-specific strategies will be developed in the near future, resulting in complete wound healing with no scar tissue formation.